2014
DOI: 10.1371/journal.pone.0106976
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow-Derived Mesenchymal Stem Cells Drive Lymphangiogenesis

Abstract: It is now well accepted that multipotent Bone-Marrow Mesenchymal Stem Cells (BM-MSC) contribute to cancer progression through several mechanisms including angiogenesis. However, their involvement during the lymphangiogenic process is poorly described. Using BM-MSC isolated from mice of two different backgrounds, we demonstrate a paracrine lymphangiogenic action of BM-MSC both in vivo and in vitro. Co-injection of BM-MSC and tumor cells in mice increased the in vivo tumor growth and intratumoral lymphatic vesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…S5), however, suggesting either a very early requirement for Cx43 in LECs or their precursors, before the Lyve-1 promoter is active, or that the Cx43 −/− -specific defects were due to the absence of Cx43 from a non-LEC cell-type. Cx43 is known to be expressed by mesenchymal stem cells, which can affect lymphangiogenesis (Valiunas et al, 2004; Buttler et al, 2013; Maertens et al, 2014), as well as macrophages and lymphocytes (Glass et al, 2015), which have been implicated in pathological lymphangiogenesis (Betterman and Harvey, 2016). In addition, Cx43 expression in thymic regulatory T cell precursors enhances the production of Foxp3 + regulatory T cells (Kuczma et al 2011), a population of cells which were recently shown to modulate lymphedema and promote lymphatic vessel function (Gousopoulos et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…S5), however, suggesting either a very early requirement for Cx43 in LECs or their precursors, before the Lyve-1 promoter is active, or that the Cx43 −/− -specific defects were due to the absence of Cx43 from a non-LEC cell-type. Cx43 is known to be expressed by mesenchymal stem cells, which can affect lymphangiogenesis (Valiunas et al, 2004; Buttler et al, 2013; Maertens et al, 2014), as well as macrophages and lymphocytes (Glass et al, 2015), which have been implicated in pathological lymphangiogenesis (Betterman and Harvey, 2016). In addition, Cx43 expression in thymic regulatory T cell precursors enhances the production of Foxp3 + regulatory T cells (Kuczma et al 2011), a population of cells which were recently shown to modulate lymphedema and promote lymphatic vessel function (Gousopoulos et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are a population of pluripotent progenitor cells that originate from bone marrow or other tissues, such as adipose tissue and cord blood, and play a crucial role in lung cancer cell growth, metastasis 14 . Over the past decade, MSCs are increasingly being used in tissue engineering and cell-based therapies in all fields, including novel therapeutic strategy for a variety of lung diseases, in which BMMSCs are the most studied cell therapy 24 , 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Human BMMSCs from a physiologic bone environment can home to orthotopically implanted primary human breast tumors 12 , and promote breast cancer metastasis when mixed with human breast carcinoma cells 13 . Thus, BMMSCs stimulate lymphangiogenesis in physiological and pathological (malignant tumor) conditions 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In order to make further advances in the fields of tissue engineering and regenerative medicine as well as to address questions related to the lymphatic spread of tumour cells, a better understanding of the underlying mechanisms of lymphangiogenesis and the interactions between LEC, other cells, and in particular stem cells is needed. In contrast to the well‐characterized interactions between MSC and BEC, to the best of our knowledge, the paracrine interactions between MSC and LEC have not been studied in detail using primary human cells until now . Therefore, the aim of this study was to evaluate the in vitro interactions of LEC and MSC as a basis for further lymphangiogenesis and metastasis research.…”
Section: Introductionmentioning
confidence: 99%